Vaccines for preventing influenza in the elderly - Demicheli, Vittorio (Cochrane Database Syst Rev, 2018)
BACKGROUND: The consequences of influenza in the elderly (those age 65 years or older) are complications, hospitalisations, and death. The primary goal of influenza vaccination in the elderly is to reduce the risk of death among people who are most vulnerable. This is an update of a review published in 2010. Future updates of this review will be made only when new trials or vaccines become available. Observational data included in previous versions of the review have been retained for historical reasons but have not been updated because of their lack of influence on the review conclusions. OBJECTIVES: To assess the effects (efficacy, effectiveness, and harm) of vaccines against influenza in the elderly. SEARCH METHODS: We searched the Cochrane Central Register of Controlled Trials (CENTRAL) (the Cochrane Library 2016, Issue 11), which includes the Cochrane Acute Respiratory Infections Group's Specialised Register; MEDLINE (1966 to 31 December 2016); Embase (1974 to 31 December 2016); Web of Science (1974 to 31 December 2016); CINAHL (1981 to 31 December 2016); LILACS (1982 to 31 December 2016); WHO International Clinical Trials Registry Platform (ICTRP; 1 July 2017); and ClinicalTrials.gov (1 July 2017). SELECTION CRITERIA: Randomised controlled trials (RCTs) and quasi‐RCTs assessing efficacy against influenza (laboratory‐confirmed cases) or effectiveness against influenza‐like illness (ILI) or safety. We considered any influenza vaccine given independently, in any dose, preparation, or time schedule, compared with placebo or with no intervention. Previous versions of this review included 67 cohort and case‐control studies. The searches for these trial designs are no longer updated. DATA COLLECTION AND ANALYSIS: Review authors independently assessed risk of bias and extracted data. We rated the certainty of evidence with GRADE for the key outcomes of influenza, ILI, complications (hospitalisation, pneumonia), and adverse events. We have presented aggregate control group risks to illustrate the effect in absolute terms. We used them as the basis for calculating the number needed to vaccinate to prevent one case of each event for influenza and ILI outcomes. MAIN RESULTS: We identified eight RCTs (over 5000 participants), of which four assessed harms. The studies were conducted in community and residential care settings in Europe and the USA between 1965 and 2000. Risk of bias reduced our certainty in the findings for influenza and ILI, but not for other outcomes. Older adults receiving the influenza vaccine may experience less influenza over a single season compared with placebo, from 6% to 2.4% (risk ratio (RR) 0.42, 95% confidence interval (CI) 0.27 to 0.66; low‐certainty evidence). We rated the evidence as low certainty due to uncertainty over how influenza was diagnosed. Older adults probably experience less ILI compared with those who do not receive a vaccination over the course of a single influenza season (3.5% versus 6%; RR 0.59, 95% CI 0.47 to 0.73; moderate‐certainty evidence). These results indicate that 30 people would need to be vaccinated to prevent one person experiencing influenza, and 42 would need to be vaccinated to prevent one person having an ILI. The study providing data for mortality and pneumonia was underpowered to detect differences in these outcomes. There were 3 deaths from 522 participants in the vaccination arm and 1 death from 177 participants in the placebo arm, providing very low‐certainty evidence for the effect on mortality (RR 1.02, 95% CI 0.11 to 9.72). No cases of pneumonia occurred in one study that reported this outcome (very low‐certainty evidence). No data on hospitalisations were reported. Confidence intervaIs around the effect of vaccines on fever and nausea were wide, and we do not have enough information about these harms in older people (fever: 1.6% with placebo compared with 2.5% after vaccination (RR 1.57, 0.92 to 2.71; moderate‐certainty evidence)); nausea (2.4% with placebo compared with 4.2% after vaccination (RR 1.75, 95% CI 0.74 to 4.12; low‐certainty evidence)). AUTHORS' CONCLUSIONS: Older adults receiving the influenza vaccine may have a lower risk of influenza (from 6% to 2.4%), and probably have a lower risk of ILI compared with those who do not receive a vaccination over the course of a single influenza season (from 6% to 3.5%). We are uncertain how big a difference these vaccines will make across different seasons. Very few deaths occurred, and no data on hospitalisation were reported. No cases of pneumonia occurred in one study that reported this outcome. We do not have enough information to assess harms relating to fever and nausea in this population. The evidence for a lower risk of influenza and ILI with vaccination is limited by biases in the design or conduct of the studies. Lack of detail regarding the methods used to confirm the diagnosis of influenza limits the applicability of this result. The available evidence relating to complications is of poor quality, insufficient, or old and provides no clear guidance for public health regarding the safety, efficacy, or effectiveness of influenza vaccines for people aged 65 years or older. Society should invest in research on a new generation of influenza vaccines for the elderly.